2018
DOI: 10.5507/bp.2018.014
|View full text |Cite
|
Sign up to set email alerts
|

Risks and protective factors for triple negative breast cancer with a focus on micronutrients and infections

Abstract: Triple negative breast cancer (TNBC) is an aggressive form of breast cancer (BC) with a poor prognosis. Second, patients cannot benefit from targeted therapy, except for those with BRCA1/2 mutations, for whom poly (ADP-ribose) polymerase (PARP) inhibition therapy using olaparib has recently been approved. As global priorities continue to be epidemiological analysis of BC risk factors and early diagnosis, this review focuses on the risks and protective factors associated with TNBC. A PubMed keyword search for n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 55 publications
(60 reference statements)
1
7
0
Order By: Relevance
“…According to the present results, the highest protective effect of green tea was found in BC recurrence prevention. This is in line with previous studies, where the authors demonstrated an anti-neoplastic effect of green tea through a reduction in viability and proliferation of BC cells [77,78,79]. In particular, a previous review on epigenetic modification by epigallocatechin on BC cell lines revealed a significantly greater inhibition of BC cell growth.…”
Section: Discussionsupporting
confidence: 90%
“…According to the present results, the highest protective effect of green tea was found in BC recurrence prevention. This is in line with previous studies, where the authors demonstrated an anti-neoplastic effect of green tea through a reduction in viability and proliferation of BC cells [77,78,79]. In particular, a previous review on epigenetic modification by epigallocatechin on BC cell lines revealed a significantly greater inhibition of BC cell growth.…”
Section: Discussionsupporting
confidence: 90%
“… 77 On the other hand, it is important to highlight that the presence of EBV alone is not shown to be associated with tumor stage, histological grade, molecular subtypes or nodal status; as previously reported by other investigations. 78 However, HPVs and EBV have been considered as risk factors for TNBC; 79 we found a significant association between HPVs and EBV co-presence and TNBC as well as luminal A subtypes. Moreover, studies showed co-presence of HPVs and EBV to be correlated with advanced breast Nottingham histological grade 65 and aggressive phenotype.…”
Section: Discussionmentioning
confidence: 59%
“…For instance, B3GNT5 is elevated in acute myelocytic leukemia, ovarian cancer and glioblastoma compared to healthy controls [44][45][46]. In TNBC, ST3GAL4 and ST3GAL6 were implicated in hypoxia and nutrient deprivation-induced glycosylation change and aggressiveness in TNBC [47][48][49]. UGT8 was previously reported as a potential oncogene in basal-like BC, where inhibition of UGT8 expression suppresses basal-like BC via regulating the sulfatide-αVβ5 axis [50].…”
Section: Discussionmentioning
confidence: 99%